2007
DOI: 10.1063/1.2717867
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties of n-type nanocrystalline bismuth-telluride-based thin films deposited by flash evaporation

Abstract: The thermal conductivity of n-type nanocrystalline bismuth-telluride-based thin films (Bi2.0Te2.7Se0.3) is investigated by a differential 3ω method at room temperature. The nanocrystalline thin films are grown on a glass substrate by a flash evaporation method, followed by hydrogen annealing at 250 °C. The structure of the thin films is studied by means of atomic force microscopy, x-ray diffraction, and energy-dispersive x-ray spectroscopy. The thin films exhibit an average grain size of 60 nm and a cross-plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(41 citation statements)
references
References 22 publications
2
38
0
1
Order By: Relevance
“…There are presently many deposition methods to obtain thermoelectric thin films with high quality [7][8][9][10][11]. These thin film fabrication methods are able to produce high thermoelectric performance, but it is challenging to reduce their fabrication cost due to the waste produced in a normal etch-based process and the film thickness which is proportion to deposition time.…”
Section: Introductionmentioning
confidence: 99%
“…There are presently many deposition methods to obtain thermoelectric thin films with high quality [7][8][9][10][11]. These thin film fabrication methods are able to produce high thermoelectric performance, but it is challenging to reduce their fabrication cost due to the waste produced in a normal etch-based process and the film thickness which is proportion to deposition time.…”
Section: Introductionmentioning
confidence: 99%
“…70 nm). It was found that S 2 σ is about 6.2 x 10 -4 W/m-K 2 at 300 K which is a factor of 10 larger than the value reported for ntype Bi 2 Te 3 single nanowires [37] and a factor of 3 smaller than nanocrystalline Bi 2 Te 3 [38] (all these power factors were measured at similar σ).…”
Section: Nanostructured Materials For Solar Thermoelectric Generatorsmentioning
confidence: 76%
“…Our flash evaporation equipment contains a powder vessel with a guide, a tungsten boat for evaporation, and a substrate holder in a vacuum chamber. [32][33][34][35] The distance between the tungsten boat and the substrate is 30 mm. The tungsten boat contains a slight pocket (50 mm length, 10 mm width, 2 mm depth) to prevent the powders from spilling out from the boat.…”
Section: Methodsmentioning
confidence: 99%